Blood pressure in adults with cerebral palsy: a systematic review and meta-analysis of individual participant data. Issue 10 (October 2021) - Noten, Suzie; van den Berg-Emons, Rita J.G.; Thorpe, Deborah E.; Heyn, Patricia C.; Marciniak, Christina M.; McPhee, Patrick G.; Lamberts, Robert P.; Langerak, Nelleke G.; Verschuren, Olaf; Salokivi, Tommi; Morrison, Katherine M.; Peterson, Mark D.; et al.
Abstract : Objectives: This systematic review and meta-analysis was designed to determine the overall mean blood pressure and prevalence of hypertension among a representative sample of adults living with cerebral palsy by combining individual participant data. Additional objectives included estimating variations between subgroups and investigating potential risk factors for hypertension. Methods: Potential datasets were identified by literature searches for studies published between January 2000 and November 2017 and by experts in the field. Samples of adults with cerebral palsy ( n  ≥ 10, age ≥ 18 years) were included if blood pressure data, cerebral palsy-related factors (e.g. cerebral palsy subtype), and sociodemographic variables (e.g. age, sex) were available. Hypertension was defined as at least 140/90 mmHg and/or use of antihypertensive medication. Results: We included data from 11 international cohorts representing 444 adults with cerebral palsy [median (IQR) age of the sample was 29.0 (23.0–38.0); 51% men; 89% spastic type; Gross Motor Function Classification System levels I–V]. Overall mean SBP was 124.9 mmHg [95% confidence interval (CI) 121.7–128.1] and overall mean DBP was 79.9 mmHg (95% CI 77.2–82.5). Overall prevalence of hypertension was 28.7% (95% CI 18.8–39.8%). Subgroup analysis indicated higher blood pressure levels or higher prevalence of hypertension in adults with cerebral palsy above 40 years of age, men, those with spastic cerebral palsy or those who lived in Africa. BMI, resting heart rate and alcohol consumption were risk factors that were associated with blood pressure or hypertension. Conclusion: Our findings underscore the importance of clinical screening for blood pressure in individuals with cerebral palsy beginning in young adulthood. Abstract : Supplemental Digital Content is available in the text